Crystal chemistry and compressibility of Fe0.5Mg0.5Al0.5Si0.5O3 and FeMg0.5Si0.5O3 silicate perovskites at pressures up to 95 GPa - Koemets, Iuliia; Wang, Biao; Koemets, Egor; Ishii, Takayuki; Liu, Zhaodong; McCammon, Catherine; Chanyshev, Artem; Katsura, Tomo; Hanfland, Michael; Chumakov, Alexander; Dubrovinsky, Leonid (Frontiers in Chemistry, 2023)
Silicate perovskite, with the mineral name bridgmanite, is the most abundant mineral in the Earth’s lower mantle. We investigated crystal structures and equations of state of two perovskite-type Fe3+-rich phases, FeMg0.5Si0.5O3 and Fe0.5Mg0.5Al0.5Si0.5O3, at high pressures, employing single-crystal X-ray diffraction and synchrotron Mössbauer spectroscopy. We solved their crystal structures at high pressures and found that the FeMg0.5Si0.5O3 phase adopts a novel monoclinic double-perovskite structure with the space group of P21/n at pressures above 12 GPa, whereas the Fe0.5Mg0.5Al0.5Si0.5O3 phase adopts an orthorhombic perovskite structure with the space group of Pnma at pressures above 8 GPa. The pressure induces an iron spin transition for Fe3+ in a (Fe0.7,Mg0.3)O6 octahedral site of the FeMg0.5Si0.5O3 phase at pressures higher than 40 GPa. No iron spin transition was observed for the Fe0.5Mg0.5Al0.5Si0.5O3 phase as all Fe3+ ions are located in bicapped prism sites, which have larger volumes than an octahedral site of (Al0.5,Si0.5)O6.